Stocking and yield potential of three different logging systems in a shelterwood cut of Nothofagus pumilio forest - Cellini, Juan Manuel; Martínez-Pastur, Guillermo; Spagarino, Carlos; Peri, Pablo Luis; Vukasovic, Ricardo (BOSQUE, 2017)
Nothofagus pumilio is the most important timber native species of south Patagonia in Argentina and Chile. Total volume stock and timber production change according to site quality, occupation degree, growth development phases and management history of the stands. The aim of this work was to evaluate the yield of three different logging systems (short-logs, long-logs and full stems) under a shelterwood cut system of N. pumilio forest growing at a middle site quality stand in Tierra del Fuego (Argentina). Sample plots were obtained in an old-growth two strata stand (3.0 ha) with abundant regeneration (stand density index of 93.8-113.4 %). Total volumes per hectare varied between 726.5 and 850.3 m3 ha-1. The volume/basal area ratio varied from 11.8 to 12.1 m3 m-2. Yield indexes obtained were 45.5 % for full stems, 21.3 % for long-logs and 22.4 % for short-logs logging systems. A model performed to estimate the timber volume for each system shows that full stems is significantly different from the other two. Several studies related to timber production were compared and discussed. Thus, applying full stems system results in a higher timber volume. Considering new alternatives in the planning of N. pumilio forests allows for higher harvest rates, increasing profits for the forestry company and minimizing the damage to the forest.